Proving Grounds: How Saudi Arabia Shaped Computer Aided Design Tools Used by American Architects, 1967–83. - Tobey, Aaron (Technology & Culture, 2025)
This article reinterprets the early history of computer-aided design (CAD) by relocating its development from U.S. labs to transnational building sites in Saudi Arabia. Drawing on unpublished project records and planning documents, the article shows how American architectural firms working on Saudi-funded megaprojects shaped the routines, software, and visual language of CAD. By framing CAD as a product of geopolitical negotiation—rather than technical inevitability—this article unsettles dominant digital-turn narratives. This analysis contributes to architectural history, STS, and digital studies by demonstrating how design tools emerged through the entanglement of labor, software, and political ambition.